Effectiveness of Motor Relearning Program in Improving Walking Ability of Post-Stroke Patients: Meta-Analysis - Umardi, Syazana Zahra; Muktabar, Hilmi Ega; Sadin, Salsabila Saufia Aura; Khan, Amre Alfarif; 'Azzah, Taqiyyah Nurul; Kholifah, Annisa Nur; Pristianto, Arif (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Stroke is a disorder of brain function due to rupture or blockage of blood vessels in the brain. To collect and analyze previous studies related to the improvement of walking ability of post-stroke patients with MRP intervention compared with functional training. Methods: The meta-analysis method by sourcing seven research articles that were searched using PICO criteria consisting of population, namely post-stroke patients, intervention provided, namely Motor Relearning Program, and comparisons in the form of functional training with outcomes of improved walking ability. Keywords used in searching articles are “Motor Relearning Program”, “stroke”, and “randomised controlled trial” through a database in the form of Google Scholar. Data was processed using the Review Manager application (RevMan 5.3). Results: There was an increase in walking ability in stroke patients who were given a motor relearning program by 1.83 units compared to patients who were given functional training (SMD = 1.83; 95% CI = 0.01 to 3.65) and the results were statistically significant (p <0.00001). The heterogeneity of the study data showed I2= 97% (random effect model). Conclusion: A Motor Relearning Program (MRP) is more effective than functional training in improving walking ability in post-stroke patients.